ChemInform Abstract: Chincona Alkaloid‐Catalyzed Enantioselective Trifluoromethylthiolation of Oxindoles. Issue 8 (February 2015) - Yang, Tao; Shen, Qilong; Lu, Long
Abstract using trifluoromethyl‐substituted thioperoxide as electrophilic trifluoromethylthiolating reagent